AB0162 Klrg1 expression is reduced on nk cells from sle patients and inversely correlates with disease activity and clinical features. (12th June 2018) - Novelli, L.; Barbati, C.; Ceccarelli, F.; Vomero, M.; Perricone, C.; Morello, F.; Garufi, C.; Spinelli, F.R.; Alessandri, C.; Valesini, G.; Conti, F.
Abstract : Background: Systemic Lupus Erythematosus (SLE) is a multifactorial autoimmune disease, with different immunological alterations and clinical phenotypes. Natural killer (NK) cells participate in the regulation of several immune responses but their function in SLE is not well understood. 1 KLRG1 (killer cell lectin like receptor G1) is a trans-membrane protein expressed in humans especially on NK cells, working as an inhibitory receptor of their cytotoxic activity. Thus, KLRG1-mediated signal might have a role in preventing autoimmunity, increasing the activation threshold of NK cells. 2 KLRG1 gene also, emerged as a disease susceptibility gene for SLE in four different ethnic groups. 3 Objectives: The aim of this study was to characterize KLRG1 expression on NK cells (both CD56 dim and CD56 bright ) from SLE patients compared to healthy subjects (HS) and to investigate its possible correlations with clinical features, including SLE disease activity. Methods: We enrolled 14 patients (14F, mean age±SD 37±10.7 years, mean disease duration ±SD 10.5±7.9 years) affected by SLE according to the 1997 ACR criteria, and 7 HS (7F, mean age±SD 33±5.5 years). Disease activity was measured by SLEDAI-2K. Peripheral blood mononuclear cells (PBMCs) were purified and phenotypic characterization was performed. All experiments were conducted by flow cytometry. Results: KLRG1 was expressed in a statistically significant lower amount on total NK cells from SLE patients compared to HS (p=0.0007). Analysis of CD56 dim and CD56 bright populations showed less amount of KLRG1 in SLE patients compared to HS (p=0.0051 and p=0.0068) (figure 1). The low levels of KLRG1 on NK cells inversely correlated with the SLEDAI-2K (p=0.029) and were inversely associated with the presence of arthritis (p=0.029), arthralgias (p=0.0024) and hematological disorders (p=0.025). A direct association between KLRG1 expression on NK cells and the use of HCQ was found (p=0.001). Analyzing the two main subpopulations of NK cells, we observed an inverse association between KLRG1 on CD56 dim cells and arthritis (p=0.0089), arthralgias (p=0.0001), hematological disorders (p=0.0329) and SLEDAI-2K (p=0.0105). KLRG1 on CD56 dim was directly associated with the use of HCQ (p=0.0010). KLRG1 on CD56 bright cells was also directly associated with the use of HCQ and MMF (p=0.03 and p=0.014). Conclusions: This study shows for the first time a reduced expression of KLRG1 in SLE patients. The inverse associations between the levels of this receptor on NK cells and the SLEDAI-2K and clinical features, together with the direct association with HCQ and MMF, suggest a possible role of KLRG1 in the pathogenesis of this disease. KLRG1 could be a possible therapeutic target in SLE. References: [1] Spada R, Rojas JM, Barber DF. Recent findings on the role of natural killer cells in the pathogenesis of systemic lupus erythematosus. J Leukoc Biol. 2015 Oct;98(4):479–87. [2] Henson SM, Akbar AN. KLRG1–more than a marker for T cell senescence. Age (Dordr). 2009 Dec;31(4):285–91. [3] Armstrong DL, Reiff A, Myones BL, et al. Identification of new SLE-associated genes with a two-step Bayesian study design. Genes Immun. 2009 Jul;10(5):446–56. Disclosure of Interest: None declared